PENGARUH KUALITAS KEPEMIMPINAN, KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN KANTOR DIREKSI PT HUTAHAEAN PEKANBARU - Selfia, Rahma; Zulfadil, Zulfadil; Nuryanti, Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of leadership quality, compensation andjob satisfaction on the performance of employees at the director's office of PTHutahaean Pekanbaru. The population in this study included all employees at thedirector's office of PT Hutahaean Pekanbaru. Primary data was collected using aquestionnaire as an instrument to prove the results of the study. To test thehypothesis in this study, multiple linear regression was used with the help of theSPSS 25 program.The results showed that: 1) there is a positive and significantinfluence of leadership quality on employee performance at the director's office ofPT Hutahaean Pekanbaru, 2) compensation has no effect on the performance ofemployees at the director's office at PT Hutahaean Pekanbaru, 30 job satisfactionhas no effect on the performance of employees at the office of directors of PTHutahaean Pekanbaru , 4) the quality of leadership, compensation and jobsatisfaction have a simultaneous effect on the performance of the employees of thedirectors' office of PT Hutahaean Pekanbaru. Keywords: leadership quality, compensation, job satisfaction, performance